Digitalization-Based Geometric Design of Open Pit Mining Blast Using Visual Block Programming Method (CIVED, 2024)
Gilgal Batu Alam Lestari (PT. GILBAL) is a company specializing in granodiorite rock mining. In its mining operations, PT. GILBAL employs blasting to break down materials, simplifying the loading and processing stages. The design of blast hole geometry requires precise calculations to achieve an optimal configuration, ensuring that blast fragmentation aligns with operational needs. To facilitate the blast hole geometry calculations, an application is needed that delivers accurate results and can be accessed anytime, anywhere. One approach to developing this application is through visual block programming using the Kodular tool. The research aims to design a system programming concept for an application capable of processing calculations for both blast geometry design and blast fragmentation outcomes, implementing this application program for actual blasting operations in the field, and achieving high accuracy in the application design's performance when applied in real-world field conditions. Application testing for blast hole geometry calculations demonstrated that the R.L. Ash method achieved an average accuracy of 97.39%, the C.J. Konya method reached 98.49%, the Anderson method achieved 99.93%, and the Langefors method reached 99.95%. In terms of calculating blast fragmentation, the R.L. Ash method attained an average accuracy of 89.57%, the C.J. Konya method 93.49%, the Anderson method 86.50%, and the Langefors method 99.81%.